Performance study of White Pekin ducks in different stocking density in floor rearing system - MALLICK, S B; MOHANTY, G P; MISHRA, S K; BEHERA, K; DASH, S K; SETHY, K; PATI, P K; MOHAPATRA, L M (The Indian Journal of Animal Sciences, 2018)
To study the effect of different stocking density on the performance of White Pekin ducks, 144 unsexed day-old White Pekin ducklings were reared for 42 days and on 43rd day, these duckings were distributed into four equal groups, each with three replicates in deep litter system of rearing. The floor space provided per ducking was G1 : 1,350 cm2, G2 : 1,800 cm2 , G3 : 2,250 cm2 and G4 : 2,700 cm2. The experiment continued from 7-10th weeks of age. The parameters studied were body weight, body weight gain, feed consumption, feed conversion ratio (FCR), serum biochemical profile, carcass characteristics and litter moisture content. The 7th and 8th week body weight gain of all the treated groups did not differ significantly but higher body weight of ducks were recorded in G3 and G4 groups than that of G1 and G2 groups at 9th and 10th week of age. The cumulative (7-10 weeks) body weight gain and FCR of white Pekin ducks was higher in group G3 and G4 than that of G1 and G2 groups. Cumulative feed consumption of all the treated groups of ducks did not differ significantly. No significant difference was observed in the studied serum biochemical and carcass characteristics of the treated groups. The litter moisture content was lower in G3 and G4 than that of G1 and G2 groups in all the studied periods. From this, it may be concluded that the floor space of 1,350 cm2 up to 8th week and 2,250 cm2 at 9th and 10th weeks of age per Pekin duck is suitable with respect to production performance of birds.